SEBUAH KESENJANGAN IMPLEMENTASI INTERNATIONAL FINANCIAL REPORTING STANDARS (IFRS), ANTARA TEORI, PRAKTIK DAN RISET PADA PERGURUAN TINGGI - Anuar Syahdan, Saifhul; Safriansyah, Safriansyah; Lisandri, Lisandri (Program Studi Akuntansi FPEB UPI, 2013)
Development of accounting theory is a way of theory, practice and research. Three aspects of the accounting development is an integrated whole, which would form a logical reasoning embodied in engineering financial reporting to become a Conceptual Framework. In practical terms, the adoption of IFRS is not an option for Indonesia, but must, in the hope, foreign investment will continue to enter or even increased and we are not isolated in the international arena. Nobes ( 2010) in his book states that, the International Accounting Standards have an important role in developing countries. Adoption of IFRS is the cheapest way for these countries than setting its own standards. Since January 1 st, 2012, Indonesia has adopted IFRS, there is a gap or imbalance between academics accounting practices and understanding regarding the implementation of IFRS in Indonesia. It should be encouraged readiness for accountants, auditors, management, Tax Officials, and regulators and academics to begin adjusting to the provisions of IFRS